2010
DOI: 10.1111/j.1537-2995.2010.02967.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage characteristics of cord blood progenitor cells: report of a multicenter study by the cellular therapies team of the Biomedical Excellence for Safer Transfusion (BEST) Collaborative

Abstract: Cord blood HPC collections maintained at 4 °C retained higher TNC counts, MNC counts, and CD45+ cell viability over a 72- to 96-hour storage period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 10 publications
(16 reference statements)
3
20
0
Order By: Relevance
“…Other variables that have been shown to impact PT viability include storage temperature between collection and processing, transient warming events of cryopreserved cells, thawing protocol, and the length of time between thaw and infusion . In this study, constant storage temperatures and thawing protocols were used and potential for transient warming events was minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Other variables that have been shown to impact PT viability include storage temperature between collection and processing, transient warming events of cryopreserved cells, thawing protocol, and the length of time between thaw and infusion . In this study, constant storage temperatures and thawing protocols were used and potential for transient warming events was minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the functionality of CD34+ cells can be reduced significantly after cryopreservation . In one of these studies, annexin V–negative CD34+ cells correlated with NOD/SCID mouse hematopoietic repopulating ability, indicating as would be expected that apoptotic CD34+ cells fail to engraft .…”
Section: Discussionmentioning
confidence: 98%
“…Reports by Pamphilon and colleagues and others using 7‐AAD indicated that refrigerated storage at 4°C can prolong nucleated cell viability presumably by slowing metabolism and preserving nutrient supply, particularly in mature blood cells. This was not observed for CD34+ cells where viability was assessed using 7‐AAD and annexin V staining in studies conducted by Radke and coworkers .…”
Section: Discussionmentioning
confidence: 99%
“…Different transportation strategies have been investigated [30] and a significant amount of research has been carried out to understand the effects of cold storage and cryopreservation on the viability of cells [31][32][33]. The study carried out within the research reported here has investigated the effects of the combination of cold storage and mechanical stress during cold transport of an hMSC suspension without the presence of cryoprotectant.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accord with those observed by others that the tolerance of cells to cold storage is dependent on cell type [52,53] and that only a certain subpopulation of cells will survive prolonged cold storage. [31]. Increased CD29 and CD44 expression was noticed after 24 h of 25 Hz vibration, but not at 10 Hz.…”
Section: Influence Of Cold Storage and Vibration On Stem Cell Surfacementioning
confidence: 91%